Water Condition of Tajwid Lake in the Langgam District, Pelalawan Regency, Riau Province - Prakoso, Dodo; Dahril, Tengku; Simarmata, Asmika. H. (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Tajwid Lake is an oxbow lakes that located in the Langgam District, Pelalawan Regency,Riau Province. The potency of the Tajwid Lake is currently under reviewed by the governmentof Pelalawan as it will be developed into a tourist destination. Water quality in the lake Tajwidmight be changed as a result of human activities conducted around the lake. A study aims toprovide basic information on water quality and determine the trophic status of the lake wasconducted in February 2016. There are three stations (Station 1, Station 2 and Station 3) and thewater was sampled from three depths, surface, middle and the bottom of the lake. The samplingswere conducted 3 times, once / week. The water quality parameters measured were depth,transparency, temperature, pH, free CO2-, DO, Nitrate and Phosphate concentration. Resultsshown that the depth of the lake was ranged from 6.3 to 12.3 m, transparency 51.3- 69 cm,temperature 27.7-30.3 Â°C, pH 5, dissolved oxygen 2.3-8.3 mg / L. Free carbon dioxide ranged4.9-13.9 mg / L, nitrate 0.02- 0.11 mg / L, phosphate from 0.02 to 0.1 mg /L. The Nitrate andphosphate concentrations indicate that the condition of the Tajwid Lake is between oligotrophicto mesotrophic.Keywords : Tajwid Lake, Oxbow Lake, Water Quality, Trophic Status